ASSET MANAGEMENT ANALYSIS AFTER EXPANSION BAUBAU CITY - Tasdik, Moh.; *, Haselman; Lambali, Suryadi; Ahmad, Badu (IJRDO - Journal of Applied Management Science, 2015)
The research objective was to analyze the impact of regional asset management policy on regionalexpansion Baubau City. This research was conducted in the City Baubau Southeast Sulawesi Province. Theresearch approach using qualitative research with quasi experimental method. Data collection technique usedobservation and interviews. Analysis of data through data reduction, data presentation and verification. Theresults showed that as a result of regional expansion that is less prepared and driven by the interests of powerpolitics and temporary, then the regional division of Baubau impact expansion policy is problematic, especiallyin the asset management area that is less expensive inventory of assets, legal, audit, asset valuation, assetoptimization as well as the supervision and control of assets that make it an Baubau City government has notentirely been handed over by the government Buton as a parent. This is because, due to the impact of a lessexpensive expansion of asset management application area before doing the division.